Analisis StrukturRumah Sakit Umum Intan Husada – Garut Bagian Rawat Inap - Walujodjati, Eko; Wiguna, Andreansyah (Jurnal Konstruksi, 2017)
The   construction of a building must of course be planned in accordance with the needs, which the building must have the criteria of safe, comfortable, economical, beautiful and in accordance with the designation. Intan Husada Hospital Building Kab. Garut inpatient section was built to meet the needs of the community, especially District Tarogong Kidul generally Garut regency in the inpatient care service. Building RSU Intan Husada Garut built 4 floors with most use of reinforced concrete structures. Floor plates are set 25 Mpa (f'c) and 400 Mpa (fy) concrete. For structural parts in general the columns and beams are fixed with 25 Mpa concrete and 400 Mpa (fy) steel grade. For the foundation it self set by using foot plate foundation. Planning of reinforced concrete structure refers to Indonesian National Standard (SNI) SNI 03-2847-2002 on Procedure of Planning of Concrete Structure for Building Building. Structural Analysis with recognized software tools. The result of structure analysis in the form of moment, normal and shear is used to plot elements of structure. From structural analysis that is done obtained comparison of calculation result of structural analysis with attached. Column analysis results with longitudinal reinforcement 19D22 D10-180 while the longitudinal tu-straw 20D25 stirring D10-100. Beams of analysis results with longitudinal reinforcement 2D13 and 9 D22 stirring D10-200 while the longitudinal reinforcing battles 19D22 stirring D10-100. Sloof beam analysis with longitudinal reinforcement 4D22 D8-250 while mounted longitudinal 6D22 stirring D10-100.